Distributed shape formation of multi-agent systems - Haghighi, Reza. (2013)
In region based shape control of multi-agent systems, the agents move together as a group inside a desired region while maintaining minimum distance among themselves. The desired formation is specified as the desired region for the whole group instead of desired trajectories for individual agents. One limitation of region based shape formation method is the necessity of access to the desired reference of the region i.e. desired movement of the entire group. This paper presents a distributed shape formation control method for multi-agent systems. We develop a state estimator for each agent to construct the desired reference based on local information. A Lyapunov-like function is proposed to examine the stability of the overall system. Simulation results are presented to illustrate the performance of the proposed method in distributed shape formation.